Synergistic Effects of Lauric Arginate and Peracetic Acid in Reducing Listeria monocytogenes on Fresh Apples - Shen, Xiaoye; Cong, Jian; Mugendi, Joshua; Hanrahan, Ines; Zhu, Mei-Jun (Frontiers in Microbiology, 2021)
Apples are naturally coated with a water repelling hydrophobic wax layer, which may limit antimicrobial efficacies of surface sanitizer solutions. Lauric arginate (LAE) is a cationic surfactant with antimicrobial efficacy to control Listeria monocytogenes. In this study, we investigated the antimicrobial and the wettability effects of LAE in enhancing anti-L. monocytogenes efficacy of peracetic acid (PAA) and further verified the optimized treatment combinations in a pilot spray-bar brush bed system. Apples after 48 h of inoculation were treated with PAA surface sanitation in combination of different concentrations of LAE at 22 C or 46 C. Adding 0.001% of LAE significantly increased the antimicrobial effectiveness of PAA at 22 C. A 30-120 sec wash by 80 ppm PAA with 0.01% and 0.05% LAE at 22 C reduced L. monocytogenes on apples by 2.10-2.25 and 2.48-2.58 Log10 CFU/apple, respectively. Including LAE in the PAA solution decreased contact angles on apple surfaces. However, the increased wettability of the sanitizer solution may not be the main contributor for the enhanced antimicrobial efficacy of the PAA solution. The addition of Tween 80 or Tween 85 only slightly boosted the anti-L. monocytogenes efficacy of PAA solutions, even though it decreased the contact angle changes of the PAA solution as much as LAE. The effectiveness of PAA with LAE solutions in decontaminating L. monocytogenes significantly increased with the increased concentration of PAA (60 to 80 ppm) or LAE (0.01% to 0.05%), or the treatment temperature (from 22 C to 46 C). The synergistic effects of PAA and LAE were further validated in a pilot spray-bar brush bed packing system, where a 30-sec spray wash with 80 ppm PAA and 0.05% LAE at 22 C and 46 C caused 1.68 and 2.08 log reduction of Listeria on fresh apples, respectively. This study provides an improved PAA process/preventive strategy for ensuring microbial food safety of fresh apples that is applicable to commercial apple packing lines.